(untitled) (Cadernos de Sociomuseologia, 2025)
The article aims to semiotically analyze how the discourse of racism is configured in the article “Negrinho gostou de Portinari: Museu”, published in the newspaper Diário de Notícias in 1960. From this point of view, the research articulates reflections on culture, race and museums, observing the forms of representation and social recognition present in journalistic language and visual experience. The research problem, initially, is the absence of a proper name for the black boy mentioned in the report, in contrast to the repetition of the name of Cândido Portinari, an established artist. The methodology adopted is exploratory and qualitative, based on a semiotic analysis that allows us to observe how meanings are produced and updated in the interactions between subjects and images, and documentary research, with interpretation of the journalistic text. Furthermore, the study focuses on the relationship between black children and the artworks Vendedor de Passarinhos and Menina com a Flor, in which the children construct visual metaphors that update the meanings of the images. The text shows that, although Portinari sought to represent the Brazilian people, the gaze portrayed in his works is crossed by a position of social distance. The article contributes to thinking about the symbolic mechanisms that produce racism in language, art and cultural institutions. Keywords: Negrinho; semiotics; museum; racism.